(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
The purpose of this research is an analytical analysis of the compression process (including deletion and merging) in old cinematic films compared to new cinematic films in Persian language. The old cinematic films selected for this study include two films, "Kaiser" and "Treasure of the Qaroon," and new cinematic films that examine two films," Life+1 Day "and “Lottery.” The theoretical framework has been used in Cognitive Phonology, Bybee (1999). The method of the present study is descriptive-analytical, and data collection is in library method. All the data has been pulled out from the dialouge of films, which been examined the compression process in the old and new films separately. In this research, we first examine the Utterance and discourse of the intended films in detail. At the end of the work, the elements of the Persian language are analyzed. The results indicate that the compression process in Persian language films has been araised, and in cases where more compressions have been done, their frequency has been higher. That is, in " Life+1 Day and “Lottery’s film, there are more compression processes than "Kaiser" and Treasure of the Qaroon’s film. The fact that the two categories of nouns and verbs are part of the basic entity of a phrase, such that if these categories are frequent then they are compressed or eliminated. On the other hand, the presence of an adjective, adverb, or letter to describe the replacement of noun or verb in the conceptual connection, which is sufficient to represent them, and this will support with Bybee’s view point. So the compression, deleting or merging processes in data has shown less frequently.